Effect of erythropoietin administration on the expression of brain-derived neurotrophic factor, stromal cell-derived Factor-1, and neuron-specific enolase in traumatic brain injury: A literature review. (September 2021) - Said, Muhammad Fadli; Islam, Andi Asadul; Massi, Muhammad Nasrum; Prihantono,
Abstract: Traumatic brain injury (TBI) is a major cause of death and lifelong disability around the world that predominantly affects young and middle-aged people. Erythropoietin (EPO) is a promising therapeutic agent for a variety of neurological injuries including TBI due to its neuroprotective effects. Here we review the impact of exogenous erythropoietin administration on the expression of brain-derived neurotrophic factor (BDNF), stromal cell-derived factor-1 (SDF-1), and neuron-specific enolase (NSE) levels in cerebrospinal fluid after TBI as biomarkers for neuron regeneration and survival to predict TBI outcome. Highlights: Traumatic brain injury (TBI) is a major cause of death and lifelong disability. Administration of erythropoietin (EPO) can benefit the clinical outcome of patients with TBI. EPO treatment increases BDNF and SDF-1 expression in the brain. BDNF and SDF-1 promote neuron survival and regeneration. EPO is a promising therapeutic agent with neuroprotective effects.